Identification Forgery Image and Image Operation by FCM Algorithm (Al-Mansour Journal, 2022)
Digital images are easy to manipulate and edit due to availability of powerful image processing and editing software. It is possible to add or remove important features from an image without leaving any obvious traces of tampering. The structure of detection forgery image in general, includes some of basic stages, and the most important stage is extract features from image because these features is the basic to detected if an image original or not. In this paper, we give a structural to build identification of anti-forensic detecting using steganalytic approaches feature vector. To identify image anti_forensic and image processing. Where several approaches of steganalysis that depend on feature based steganalytic, one of these is Image Quality Measured (IQM). This goal can be achieved by using Fuzzy C Mean (FCM) and Euclidian distains (EU). Results obtained from testing this system for identify forgery image and image operation was with accuracy of 94.8%.
Keywords: Forgery image; Image operation; image quality measure (IQM); Fuzzy C Mean (FCM); build identification; anti-forensic detecting